KEPRIBADIAN INTROVERT TOKOH HAKOBIYA DALAM ANIME AKUDAMA DRIVE : KAJIAN PSIKOLOGI SASTRA - Ni Luh Gede Meilantari; Ida Bagus Putu Angga Sudharta (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2024)
This research discusses and describes the inner conflict experienced by the character Hakobiya in the anime Akudama Drive. This study is of a descriptive-qualitative nature and uses data sources from the anime Akudama Drive. The theory used in this research is Carl Gustav Jung's Psychoanalysis theory. The data collection method used in this study is the observation method, where data on the inner conflicts experienced by the character Hakobiya in each episode of the anime Akudama Drive are gathered and recorded before being analyzed. The analysis method used is descriptive-qualitative, where the data is presented not in numerical form but is described and analyzed in detail. The results indicate that Hakobiya experiences inner conflict and has an introverted intuitive-feeling personality type according to Jung's theory.